Twilight hauntings - Sage, Angie (New York : Katherine Tegen Books, 2020)
Alex goes on the run from the city of Luma when it is found out she has enchanted cards which are illegal.
School Library Journal starred, February 2020
Publishers Weekly, January 2020
Kirkus Starred, December 2019
Bulletin (Center for Children's Books), February 2020
3-6
850L
Keywords: Runaway children -- Juvenile fiction; Magic -- Juvenile fiction; Runaways -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction